A health sciences researcher’s experience of manuscript review comments, 2020–2022 - Gina Joubert (South African Family Practice)
Background: Peer review frequently improves a manuscript, but authors may consider some reviewer feedback negative, inappropriate or unclear. This study aims to summarise and analyse review comments received by authors.